Projection of structure and compositions of resistance to burning polymer composite materials with flame retardants based on magnesium hydroxide - K. A. Brekhova; I. D. Simonov-Emel'yanov; A. A. Pykhtin (Тонкие химические технологии)
Objectives. To identify general principles for the design of dispersed-filled polymer composite materials (DFPCMs) with different generalized and reduced parameters, as well as types of disperse structure with high fire resistance; to develop an algorithm for the creation of non-combustible polymer composites with flame-retardant fillers.Methods. Scanning electron microscopy and laser diffraction were used to assess the shape, size, and particle size distribution of flame retardants. According to the presented classification of DFPCMs by structural principle, standard bar samples were obtained to determine the oxygen index (OI) and the fire resistance category.Results. For the MFS-2 (medium filled system) and HFS (high filled system) structure types, the maximum resistance to burning (category V-0) is achieved with a generalized parameter of ® ≤ 0.40 volume fractions; the OI value increases in 2 times (up to ~40%) in relation to the polymer matrix.Conclusions. In order to obtain a flame retardant DFPCMs (OI = 40%, category V-0) based on ethylene vinyl acetate with OI = 20% and magnesium hydroxide (brucite), the amount of water vapor released during the decomposition of the flame-retardant filler should be at least ~250 mL/g with a coke residue ~32%. A developed algorithm for calculating compositions and generalized parameters for the creation of DFPCMs having a predetermined type of disperse structure and high resistance to burning is presented.